Juxtaposing Medical Centers Using Different Questionnaires Through Score Predictors - Puga, Clara; Schleicher, Miro; Niemann, Uli; Unnikrishnan, Vishnu; Boecking, Benjamin; Brueggemann, Petra; Simoes, Jorge; Langguth, Berthold; Schlee, Winfried; Mazurek, Birgit; Spiliopoulou, Myra (Frontiers in Neuroscience, 2022)
Background: Chronic tinnitus is a clinically multidimensional phenomenon that entails audiological, psychological and somatosensory components. Previous research has demonstrated age and female gender as potential risk factors, although studies to this regard are heterogeneous. Moreover, whilst recent research has begun to identify clinical "phenotypes", little is known about differences in patient population profiles at geographically separated and specialized treatment centres. Identifying such differences might prevent potential biases in joint RCTs and allow for population-specific treatment adaptations. Method: Two German tinnitus treatment centres were compared regarding pre-treatment data distributions of their patient population bases. To identify overlapping as well as centre-specific factors, juxtaposition-, similarity-, and meta-data-based methods were applied. Results: Between centres, significant differences emerged. One centre demonstrated some predictive power of the patients of the other centre with regard to questionnaire score after treatment. Furthermore, adherence to the completion of the questionnaires was found to be an important factor in predicting post-treatment data. Discussion: Differential age and gender distributions per centre should be considered as regards RCT design and individualised treatment planning.